The dynamics of international strategy - Segal-Horn, Susan; Faulkner, David (London : International Thomson Business, 1999)
This book is about: The nature of international strategy; Issues of co-ordination; New pathways; ...
Keywords: Business; Management; Enterprises; International business enterprises -- Management; Strategic planning